2x + 2y=-2 (Dividing it by two)
x+y=-1 (By transposition)
x=-y-1
Chat with our AI personalities
-2x=2y+5 +2x -2y -2y=2x+5 /-2 y=-1/1+2.5
2y = 4x + 4y = 2x + 2
-2x + 2y = 4 is equivalent to twice -2 + y = 2 which is the equation of a straight line.
5x-2y+3z-2x-y-4z=3x-3y-z
2. If x=5 & y =3 then: 3x + 2y = 3 x 5 + 2 x 3 = 15 + 6 = 21 2x + 3y = 2 x 5 + 3 x 3 = 10 + 9 = 19 ⇒ 3x+2y exceeds 2x+3y by 21 - 19 = 2. Alternatively: 3x+2y exceeds 2x+3y by: (3x+2y) - (2x + 3y) = 3x + 2y - 2x - 3y = x - y If x=5 & y=3 then this becomes: x - y = 5 - 3 = 2